Histopathological changes in the liver of tree shrew (Tupaia belangeri chinensis) persistently infected with hepatitis B virus - Ruan, Ping (BioMed Central, 2013)
BACKGROUND: An animal model for HBV that more closely approximates the disease in humans is needed. The tree shrew (Tupaia belangeri) is closely related to primates and susceptible to HBV. We previously established that neonatal tree shrews can be persistently infected with HBV in vivo, and here present a six year follow-up histopathological study of these animals. METHODS: Group A consists of six tree shrews with persistent HBV infection, group B consists of three tree shrews with suspected persistent HBV infection, while group C consists of four tree shrews free of HBV infection. Serum and liver tissues samples were collected periodically from all animals. HBV antigen and HBV antibodies were detected by ELISA and/or TRFIA. HBV DNA in serum and in liver biopsies was measured by FQ-PCR. Liver biopsies were applied for general histopathologic observation and scoring, immunohistochemical detections of HBsAg and HBcAg, and ultrastructural observation with electron microscope technique. RESULTS: Hydropic, fatty and eosinophilic degeneration of hepatocytes, lymphocytic infiltration and hyperplasia of small bile ducts in the portal area were observed in group A. One animal infected with HBV for over six years showed multiple necrotic areas which had fused to form bridging necrosis and fibrosis, and megalocytosis. The hepatic histopathological scores of group A were higher than those of group B and C. The histopathological score correlated positively with the duration of infection. CONCLUSIONS: Hepatic histopathological changes observed in chronically HBV-infected tree shrews are similar to those observed in HBV-infected humans. The tree shrew may represent a novel animal model for HBV infection.